Exploration of Factors That Influence Information Security Education - Gouni, Ahmed Ali Otman; Saad, Amna; Ali, Siti Haryani Shaikh (International Journal of Engineering and Technology, 2018)
The improvement of knowledge is very important in information security domain. due to its positive effect on users’ information security education. It is acknowledged that security education is playing a vital role to mitigate the risk of information security incidents and breaches that faced by users through their ordinary life. Although several approaches have been proposed in information security education, yet these threats continue to increase. To assist the effort of information security education, this research explores the effective factors that have been used in the approaches of information security education, investigates the gaps, and hence, proposes new factors that can help to developing an effective approach to information security education.